(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of this study is to find out the attitudes of pupil teachers towards Teacher Eligibility Test (TET). A sample of 200 pupil-teachers studying in different B.Ed. colleges affiliated to Utkal University, Bhubaneswar participated in this study. The result of the study indicated that the students belongs to urban areas have positive attitude towards TET than rural areas students. Further, the prospective teachers of science stream have positive attitude towards TET. So it is suggested that the required resources and facilities should be given to the pupil teachers during their training to achieve educational goals.